Development and Validation of Liquid Chromatography-mass Spectrometry Method for the Determination of Intracellular Concentration of Ginkgolide A, B, C, and Bilobalide in Transporter-Expressing Cells - Yaro, Peter; Nie, Jing; Xu, Mingcheng; Zeng, Kui; Zeng, Su (Current Pharmaceutical Analysis, 2020)
Background: Terpene lactones are major components of ginkgo biloba extract which are used in cardiovascular and degenerative diseases. To study the involvement of transporters in the transport/disposition of ginkgolides A, B, C, and bilobalide, a bioanalytical assay was developed by LCMS/ MS system for the quantitation of intracellular levels of terpene lactones in cells expressing organic cation transporter 2 (OCT2). Methods: The assay involved an optimized simple sample handling with methyl tert-butyl ether for liquid-liquid extraction and reconstitution in modified dissolution solution. Pretreatment of samples with 50 μM ascorbic acid and the addition of ascorbic acid and formic acid in dissolution solution significantly reduced matrix effect and stabilized the postpreparative samples. Separations were performed by Zobrax RRHD column (extend-C18 1.8μm, 3.0 x 100mm) and acetonitrile gradient elution. The analysis was carried out in the negative ion scan mode using multiple reaction monitoring. Results: The method was validated for linearity (concentration range of 20-5000nM), accuracy (±13.1%), precision (<11.0%), recovery (94.31–105.9%), matrix effect (93.8-111.0%) and stability. Finally, the method was applied in the determination of intracellular concentrations of ginkgolides A, B, C, and bilobalide in Madin-Darby canine kidney (MDCK-mock) and MDCK-OCT2 cells in uptake study. Conclusion: The developed method was successfully validated. Results suggest that OCT2 is involved in the renal disposition of ginkgolide A, B, and bilobalide. This method would foster the study of transport mediated activity via the interaction of ginkgolides and bilobalide with cellular systems.
Keywords: bilobalide